Colonial Appropriation of Economic Authority: Dutch Control over Trade and Shipping in the Riau-Lingga Kingdom - Syahrul Rahmat; Endang Rochmiatun; Bety Bety; Ferri Yonantha (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study examines the process of economic authority appropriation by the Dutch colonialists in the Riau-Lingga Kingdom between 1830 and 1909, by analyzing a number of contracts. Instead of using physical conflict, the Dutch colonial government chose contractual agreements as an instrument to seize economic power. This research was conducted using historical research methods. The primary sources used were contracts between the Riau Lingga kingdom and the Dutch government, as well as the Perhimpunan Plakat and other sources collected from the Indonesian National Archives, digital libraries and the Balai Maklumat Pulau Penyengat. Furthermore, the historical facts findings were analyzed using a colonialism approach. This study found that the appropriation of economic power took place gradually through legal mechanisms such as customs and excise regulations, shipping permits, and symbolic regulations on the use of the royal flag. This process transformed the Sultan's position from that of an independent economic authority to a symbolic ruler under the control of the Resident of Riau. The main findings show that Dutch colonialism in Riau-Lingga was not merely political domination, but also a process of institutionalizing economic power through fiscal and shipping regulations. This research fills a gap in the historiography of political economy in the Malay maritime region and can be considered when examining colonialization in Indonesian history from a different perspective.